Expected role of management accounting within the Six Sigma methodology: case evidence. (3rd December 2009) - Rajamanoharan, Indra Devi; Collier, Paul; Wright, Brian
Drawing on International Federation of Accountants' (IFAC) conceptual framework for management accounting, this study argues that many of the principal roles in the Six Sigma (SS) DMAIC process fit closely with IFAC's four key roles for management accounting. The results showed that the SS features applicable at all phases of the DMAIC process match closely with IFAC's key roles for management accounting. At the broadest level, the case studies illustrated that the role of management accounting had undergone considerable change, in parallel with the changes that were taking place in the wider business activities with the adoption of the DMAIC management process. Changes occurred mainly in the course of project prioritisation (define phase), and in project deployment (measure phase onwards). At both stages, SS members focused on a set of standard criteria that link directly to IFAC's best practices of management accounting in terms of the 14 concepts that form part of the conceptual framework for management accounting. Therefore, the results of this study provide a common understanding of the potentially useful role that IFAC's best practice of management accounting could play in the DMAIC phases.